Molecular basis of the Li–Fraumeni syndrome: an update from the French LFS families. Issue 8 (29th May 2008) - Bougeard, G; Sesboüé, R; Baert-Desurmont, S; Vasseur, S; Martin, C; Tinat, J; Brugières, L; Chompret, A; Paillerets, B Bressac-de; Stoppa-Lyonnet, D; Bonaïti-Pellié, C; Frébourg, T; et al.
Abstract : We have performed an extensive analysis of TP53 in 474 French families suggestive of Li–Fraumeni syndrome (LFS), including 232 families fulfilling the Chompret criteria. We identified a germline alteration of TP53 in 82 families (17%), in 67/232 of the families fulfilling the Chompret criteria (29%) and in 15/242 which did not fulfil these criteria (6%). Most of the alterations corresponded to missense mutations (67%), and we identified in four families genomic deletions removing the entire TP53 locus, the promoter and the non-coding exon 1, or exons 2–10. These results represent a definitive argument demonstrating that LFS results from TP53 haplodeficiency. The mean ages of tumour onset were significantly different between patients harbouring TP53 missense mutations and other types of alterations, missense mutations being associated with a 9 year earlier tumour onset. These results confirm that missense mutations not only inactivate p53 but also have an additional oncogenic effect. Germline alterations of TP53 that lead exclusively to loss of function are therefore associated with a later age of tumour onset and the presence of such mutations should be considered in atypical LFS families with tumours diagnosed after 40 years.